Novel screening approaches for human prion diseases drug discovery. (3rd October 2019) - Moda, Fabio; Bolognesi, Maria Laura; Legname, Giuseppe
ABSTRACT: Introduction : Human prion diseases are rare fatal neurodegenerative diseases caused by the misfolding and aggregation of the prion protein in the form of infectious prions. So far, these diseases are incurable. One of the major difficulties in identifying suitable drugs is the availability of robust preclinical screening methods. All molecules identified have been screened using cell-based assays and in vivo murine models. The existence of a continuum of prion strains has hampered the identification of efficacious molecules modulating the progression of different forms of the disease. Areas covered : The advent of new in vitro screening methodologies is allowing for novel strategies to develop new compounds that could interfere with a broad range of diseases. In particular, two innovative techniques named Real Time Quaking Induced Conversion (RT-QuIC) and Protein Misfolding Cyclic Amplification (PMCA) have opened new venues for testing compounds in a rapid a reproducible way. These are discussed within. Expert opinion : For human prion diseases, one major hurdle has been a well-defined screening methodology. In other animal species, cell-based assays have been employed that could replicate animal prions indefinitely. Such a tool for human prion diseases is still missing. Therefore, the advent of RT-QuIC and PMCA has proven instrumental to overcome this limitation.